Retinal Proteoglycans Act as Cellular Receptors for Basement Membrane Assembly to Control Astrocyte Migration and Angiogenesis - Tao, Chenqi (Cell Rep, 2016)
The basement membrane is crucial for cell polarity, adhesion and motility, but how it is assembled on cell surface remains unclear. Here, we find that ablation of glycosaminoglycan (GAG) side chains of proteoglycans in the neuroretina disrupts the retinal basement membrane, leading to arrested astrocyte migration and reduced angiogenesis. Using genetic deletion and time-lapse imaging, we show that retinal astrocytes require neuronal-derived PDGF as a chemoattractive cue and the retinal basement membrane as a migratory substrate. Genetic ablation of heparan sulfates does not produce the same defects as GAG null mutants. In contrast, enzymatic removal of heparan sulfates and chondroitin sulfates together inhibits de novo laminin network assembly. These results indicate that both heparan and chondroitin sulfate proteoglycans participate in retinal basement membrane assembly, thus promoting astrocyte migration and angiogenesis.